2017
DOI: 10.14740/gr798w
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Study of Children With ROME III Functional Gastrointestinal Disorders Managed Symptomatically in a Biopsychosocial Model

Abstract: BackgroundOur study evaluated progression of and identified potential factors contributing to outcomes of ROME III defined-functional gastrointestinal disorders (FGIDs) in children treated symptomatically in a biopsychosocial model of care with a long-term follow-up.MethodsWe performed a retrospective review of pediatric patients who were diagnosed with ROME III defined-FGIDs including functional abdominal pain, functional dyspepsia, irritable bowel syndrome and abdominal migraine. Patients were managed sympto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…A prospective study has demonstrated that approximately 41.0% of children with functional abdominal pain (FAP) continued to report clinically significant abdominal pain after a mean duration of a 9-year follow-up into adolescence and young adulthood. 2,3 The pathomechanism to explain FAPDs remains unclear and multifactorial hypotheses have been suggested. 4,5 Recently many studies have suggested that low-grade intestinal inflammation is essentially involved in the underlying pathogenesis of functional gastrointestinal disorders (FGIDs).…”
Section: Introductionmentioning
confidence: 99%
“…A prospective study has demonstrated that approximately 41.0% of children with functional abdominal pain (FAP) continued to report clinically significant abdominal pain after a mean duration of a 9-year follow-up into adolescence and young adulthood. 2,3 The pathomechanism to explain FAPDs remains unclear and multifactorial hypotheses have been suggested. 4,5 Recently many studies have suggested that low-grade intestinal inflammation is essentially involved in the underlying pathogenesis of functional gastrointestinal disorders (FGIDs).…”
Section: Introductionmentioning
confidence: 99%
“…Long term studies on FGID reveal that the persistent symptoms may either change or fluctuate in severity and the patients rarely become symptom-free [18,24]. A study among children found complete improvement in 60.1%, no improvement in 10.1% and recurrence in 35.7% of the patients whereas 11.6 5% of patients reported new symptoms [25]. In our study, 3.7% of the patients reported deferent symptoms during the follow up.…”
Section: Symptom Evolutionmentioning
confidence: 38%
“…Acid suppressive medications are recommended for epigastric pain-like symptoms and prokinetic agents for postprandial symptoms (2,23). Cyproheptadine, tricyclic antidepressants, and alternative agents such as melatonin, ginger root extract, aloe vera, pepper mint oil, and even fecal transplantation have also been found to be effective (2,24,(34)(35)(36). We used cyproheptadine as initial treatment because of its reported efficacy in FAPDs, many patients having already failed on acid reducers, limitation in using metoclopramide due to black box warning and nonavailability of domperidone in the United States (34,36,37).…”
Section: Discussionmentioning
confidence: 99%
“…Cyproheptadine, tricyclic antidepressants, and alternative agents such as melatonin, ginger root extract, aloe vera, pepper mint oil, and even fecal transplantation have also been found to be effective (2,24,(34)(35)(36). We used cyproheptadine as initial treatment because of its reported efficacy in FAPDs, many patients having already failed on acid reducers, limitation in using metoclopramide due to black box warning and nonavailability of domperidone in the United States (34,36,37). Our finding that majority of patients do not improve despite being on 2 or more medications further emphasizes that FD is a recalcitrant condition, and although various treatments have been described none of them are singularly effective as was noted in our PIG/NIG of patients.…”
Section: Discussionmentioning
confidence: 99%